2006
DOI: 10.1302/0301-620x.88b4.17407
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of local recurrences of giant cell tumour in long bones after curettage and cementing

Abstract: We retrospectively studied local recurrence of giant cell tumour in long bones following treatment with curettage and cementing in 137 patients. The median follow-up time was 60 months (3 to 166). A total of 19 patients (14%) had at least one local recurrence, the first was diagnosed at a median of 17 months (3 to 29) after treatment of the primary tumour. There were 13 patients with a total of 15 local recurrences who were successfully treated by further curettage and cementing. Two patients with a second loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 19 publications
1
65
3
1
Order By: Relevance
“…As recurrences can usually be treated successfully (Vult von Steyern et al 2006), intralesional surgery is preferable. In intralesional surgery, we strongly recommend the use of cement.…”
Section: Discussionmentioning
confidence: 99%
“…As recurrences can usually be treated successfully (Vult von Steyern et al 2006), intralesional surgery is preferable. In intralesional surgery, we strongly recommend the use of cement.…”
Section: Discussionmentioning
confidence: 99%
“…Vult von Steyern et al 19 reported that 13 patients with a total of 15 local recurrences were successfully treated by further curettage and cementation. Two of the patients with a second local recurrence were consequently treated twice.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of local recurrence, lung metastasis after treatment of primary GCT, and malignant transformation have been described 1,2,6,7,[13][14][15][16] . However, the clinical behavior of recurrent GCT, treatment strategy, and the factors affecting the clinical outcome has not been fully ellucidated [17][18][19][20][21][22] . In this multi-center study by the Eastern Asian Musculoskeletal Oncology Group (EAMOG), we retrospectively investigate the prognosis for 110 patients with recurrent GCT of bone in the extremities, and we examine the potential factors affecting the clinical outcome of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The distal radius is the third most common location for giant cell tumor of bone after the distal femur and proximal tibia, accounting for approximately 10% to 15% of cases [10,27,29,30,40]. Numerous authors have identified the distal radius as being particularly prone to recurrence [2,8,10,13,16,21,30,[36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Intralesional excision preserves the joint but even if used in combination with surgical adjuvants has a reasonably high risk of local recurrence [18,28,30,36]. Variables reported to influence local recurrence include the Campanacci grade [2,18,22,27,30,34], pathologic fracture [27,30,40], tumor location [2,13,16,27,36,39,40], type of adjuvant used [2, 7, 10-12, 16, 17, 25, 27, 30, 32, 35, 36, 38], and treatment of a primary versus a recurrent tumor [2,27,38].…”
Section: Introductionmentioning
confidence: 99%